Synthesis and characterization of dendritic polypyrrole silver nanocomposite and its application as a new urea biosensor - Pandey A.K.; Pandey P.C.; Agrawal N.R.; Das I. (My University, 2025)
Polypyrrole and its silver nanocomposite were electrochemically synthesized from aqueous solutions containing pyrrole, potassium chloride (KCl) (system A); pyrrole, KCl, and an anionic surfactant sodium dodecyl sulphate (NaDS) (system B); and pyrrole, silver nitrate, NaDS (system C). Compact and dendritic patterns were observed depending on experimental conditions. The aggregates were characterized by powder X-ray diffraction, energy-dispersive X-ray spectroscopy, scanning electron microscopy, high resolution transmission electron microscopic (HRTEM), and thermal studies (TG/DTG). HRTEM studies indicate that the particle size of PPy-Ag nanocomposite is ~30 nm. TG studies revealed that systems B and C, have different thermal behavior. Potassium ion selective electrodes were constructed using systems A, B, and C. The electrode prepared with PPy-Ag nanocomposite showed nernstian behavior with maximum slope of 57 mV. NH+4 ion-selective electrode was also constructed for this system based on nonactinimpregnated PVC matrix membrane. Urease enzyme was immobilized at the surface of as made NH+4 ion-selective electrode to develop urea biosensor showing good detection limit. © 2017 Wiley Periodicals, Inc.